Before and After Segregation and Apartheid: A Comparative Analysis - Leland Ware (The Thinker)
This article compares conditions in South Af rica before and after apartheid to the circumstances in America during and after segregation. During the eras of segregation and apartheid, conditions for Black people in America and South Af rica were oppressive in the extreme. The two systems had some differences, but the overall impact was the same.